Intra and Inter Cluster Studies for Quantitative Traits in Garlic (Allium sativum L) (SAARC Journal of Agriculture, 2014)
Garlic is propagated vegetatively, the clonal selection is the important breeding method and very scanty work has been done on the association between different traits in garlic. Analysis of variance revealed significant divergence in fifteen garlic clone with checks i. e. Yamuna Safed (G-1), Agrifound White (G-41), Yamuna Safed-2 (G-50) and Yamuna Safed-3 (G-282) for different traits, indicating sufficient genetic diversity among the cultivars. Genotypes belonging to the cluster with maximum inter cluster distance were genetically more divergent. Therefore, it is suggested that based upon large cluster distances to select genotypes from all the clusters, which may lead to broad spectrum of favorable genetic variability for bulb yield improvement. Cluster-III had highest value of plant height (93.05 cm), bulb diameter (4.71 cm), bulb size index (16.08 cm2), 20 bulb weight (700 g), clove diameter (1.75 cm), clove size index (4.43 cm2), weight of 50 cloves (97.50 g) and gross yield (159.63 t ha-1) and minimum neck thickness (1.45 cm) number of cloves per bulbs (17) days for bulb initiation (61.66 days) and days to harvesting (149.83). The traits total soluble solids contributed maximum (20.46%) toward genetic divergence followed by gross yield (16.37%), bolters (12.86%), marketable yield (11.11%), number of cloves per bulbs (10.52%), weight of 50 cloves (10.52%), days for bulb initiation (10.52%) and days for harvesting (4.09%). These traits were considered to be most important for genetic divergence, they contributed (96.45%) towards genetic divergence and selection of genotypes based on these traits will contribute to wider genetic diversity in the existing gene pool of garlic genotypes. DOI: http://dx.doi.org/10.3329/sja.v11i2.18402 SAARC J. Agri., 11(2): 61-67 (2013)